Elastofibroma presented as shoulder pain in an amateur swimmer: screening for referral in physiotherapy. A case report. (2nd December 2022) - Brindisino, Fabrizio; Mourad, Firas; Maselli, Filippo
ABSTRACT: Elastofibroma is a benign and rare fibroblast/myofibroblast tumor usually located near the periosteum of the ribs. Patients with elastofibroma can remain asymptomatic or can experience a clicking sensation during shoulder movements, shoulder stiffness, scapular and shoulder pain and dysfunction. Importantly, the symptoms can mimic a musculoskeletal condition being mistaken for orthopedic shoulder joint disease. A 54 years-old amateur swimmer self-referred to physiotherapy for left subscapular and shoulder pain. Concerns from the patient's history that caused suspicion of a medical condition included an insidious onset of nagging deep pain that increased with upper limb exertion and an audible thoracic clunk at arm end range flexion. Deep palpatory examination revealed a mass below the latissimus dorsi and rhomboids further screened by the physiotherapist with Rehabilitative Ultrasound Imaging. The physiotherapist referred the patient to a thoracic surgeon who removed the mass. After an exercise-based physiotherapy management program, the patient returned to previous activities including swimming after 5 months. The challenge for clinicians is to screen patients in whom shoulder pain may be related to non-musculoskeletal conditions. Prompt referral of patients presenting with the suspicion of elastofibroma to an appropriate physician may lead to a timely diagnosis and could avoid expensive and unnecessary rehabilitation procedures.